Pengaruh antara Loneliness dan Budaya Fear of Missing Out dengan Quarter Life Crisis pada Civitas Akademik Statistika Unisba - Jasmine Azalia Pangesti; Mahdy, Ilham Faishal (Bandung Conference Series: Statistics, 2024)
Abstract. Quarter Life Crisis phase is a phase that occurs by a person with an age range of 20 - 40 years. In this phase, a person often experiences anxiety and uncertainty of goals, plans. This Quarter Life Crisis phase can cause a person to feel anxious about the future and tend to compare their lives with the lives of others or what is usually called Fear of Missing Out (FOMO). FOMO or a condition where a person feels that other people's lives are more fun and causes a person to lock themselves up. Because of this, the person can lead to experiencing Loneliness. So the purpose of this study is to see the influence or impact between FOMO (Fear of missing Out), Loneliness, and Quarter Life Crisis on the academic community of statistics at the Islamic University of Bandung. By using Path Analysis, it is concluded that Quarter Life Crisis has a positive effect on Fear of Missing Out (FOMO) and Fear of Missing Out (FOMO) has a positive effect on Loneliness. Therefore, the Quarter Life Crisis phase can cause someone to experience Fear of Missing Out (FOMO) and someone who experiences Fear of Missing Out (FOMO) can cause Loneliness. Abstrak. Fase Quarter Life Crisis adalah fase yang terjadi oleh seseorang dengan rentang usia 20 – 40 tahun. Pada fase ini, seseorang sering kali mengalami kecemasan dan ketidakpastian tujuan, rencana. Fase Quarter Life Crisis ini dapat menyebabkan seseorang merasa cemas akan masa depan dan cenderung membandingkan hidup mereka dengan kehidupan orang lain atau yang biasanya disebut dengan Fear of Missing Out (FOMO). FOMO atau kondisi dimana seseorang merasa kehidupan orang lain lebih menyenangkan dan mengakibatkan seseorang mengurung diri. Karena hal tersebut orang tersebut bisa mengarahkan mengalami Loneliness. Sehingga tujuan dari penelitian ini adalah untuk melihat pengaruh atau dampak antara FOMO (Fear of missing Out), Loneliness, dan Quarter Life Crisis pada civitas akademik statistika Universitas Islam Bandung. Dengan menggunakan Analisis Jalur didapat kesimpulan bahwa Quarter Life Crisis berpengaruh positif terhadap Fear of Missing Out (FOMO) dan Fear of Missing Out (FOMO) berpengaruh positif terhadap Loneliness. Oleh karena itu, fase Quarter Life Crisis dapat menyebabkan seseorang mengalami Fear of Missing Out (FOMO) dan seseorang yang mengalami Fear of Missing Out (FOMO) dapat menyebabkan Loneliness.